Russia's Arctic strategy through 2035 : grand plans and pragmatic constraints - Kluge, Janis; Paul, Michael (2020)
Zusammenfassung: Russia has adopted a development strategy for the Arctic for the period from October 2020 to 2035. Reflecting hopes and perceived threats associated with the successive warming of the Arctic, it aims to advance development of the region's abundant resources, first and foremost oil and gas, and improve living conditions for the population. In the longer term, the Kremlin hopes to establish the Northern Sea Route as a new global shipping artery. Moscow also worries that an increasingly ice-free Arctic could create new territorial vulnerabilities in its Far North, and is responding by rebuilding its military presence there. Finally, Moscow also wants to preserve the region's ecological balance. The indications are, however, that the interests of the energy sector and the military will be served, while funding to improve environmental protections and living conditions will remain inadequate